INFLUENCE FACTORS OF CONSUMERS' DECISION-MAKING: THE BEHAVIORAL PERSPECTIVE ON CAR BUYING FATORES DE INFLUÊNCIA DA TOMADA DE DECISÃO DO CONSUMIDOR: A PERSPECTIVA COMPORTAMENTAL DA COMPRA DE CARRO - Furtado G.F. (2023)
© 2023 Universidade Nove de Julho-UNINOVE. All rights reserved.Objective: This study aimed to decide whether to buy a car in Brazil. It uses quantitative, descriptive methods and involves customers of six car dealerships in the cities of the states Brazilian. Method: This is a field study using quantitative, descriptive methods and involving customers of six car dealerships in the cities of the Brazilian states covered in Table 5 who purchased vehicles between 2011 and 2018. Data was collected through an electronic questionnaire. Four hundred and twenty-seven people responded to the questionnaire, which - was made when purchasing a car. For this study, only complete questionnaires were considered (n. = -demographic profile was as follows: aged between 32 and 73 years; male; belonging to social strata B1, B2, and C1; with limited financing experience; and indicating the family as the main factor in the decision to purchase the car. Originality/Relevance: Based on the information gathered, by confirming the purchase of an automobile almost immediately, often impulsively, consumers can end up with unnecessary debt. They are exacerbated by a need for more accurate information provided to the consumer when financing is attained. Results: The information obtained through the study shows a series of factors influencing the decision to purchase a car through financing. The main factors were age, average income, previous experience with financing as a means of acquiring assets, the influence of family or work, length of time taken to confirm the purchase after approval of the loan, the desire to own the car, euphoria, and happiness after purchase, easy access to financing, the level of debt after the purchase, and the degree of satisfaction with the purchase. Theoretical Contributions: The information obtained through the study shows a series of factors influencing the decision to purchase a car through financing. The main factors were age, average income, previous experience with financing as a means of acquiring assets, the influence of family or work, length of time taken to confirm the purchase after approval of the loan, the desire to own the car, euphoria, and happiness after purchase, easy access to financing, the level of debt after the purchase, and the degree of satisfaction with the purchase.